Harm Reduction Services for People Who Use Drugs: Exploring Data Collection, Evidence Gaps, and Research: Proceedings of a Workshop–in Brief - National Academy of Medicine; National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2024)
Given the public health emergency posed by drug overdoses, there have been calls for a comprehensive approach to drug policy that would include focusing on reducing harm for people who use drugs. To explore data collection efforts, evidence gaps, and research needs for harm reduction, the National Academies of Sciences, Engineering, and Medicine hosted a virtual workshop on January 30-31, 2024, sponsored by the Office of National Drug Control Policy, Executive Office of the President. The workshop focused on harm reduction strategies and services that aim to prevent overdose and infectious disease transmission; enhance the health, safety, and well-being of people who use drugs; and offer low-threshold options for accessing substance use disorder treatment. This Proceedings of a Workshop-in Brief summarizes the presentations and discussions that occurred at the workshop.

Safe Work in the 21st Century: Education and Training Needs for the Next Decade's Occupational Safety and Health Personnel - Institute of Medicine (The National Academies Press, 2000)
Despite many advances, 20 American workers die each day as a result of occupational injuries. And occupational safety and health (OSH) is becoming even more complex as workers move away from the long-term, fixed-site, employer relationship. This book looks at worker safety in the changing workplace and the challenge of ensuring a supply of top-notch OSH professionals. Recommendations are addressed to federal and state agencies, OSH organizations, educational institutions, employers, unions, and other stakeholders. The committee reviews trends in workforce demographics, the nature of work in the information age, globalization of work, and the revolution in health care delivery2014exploring the implications for OSH education and training in the decade ahead. The core professions of OSH (occupational safety, industrial hygiene, and occupational medicine and nursing) and key related roles (employee assistance professional, ergonomist, and occupational health psychologist) are profiled2014how many people are in the field, where they work, and what they do. The book reviews in detail the education, training, and education grants available to OSH professionals from public and private sources.

Going the Distance?: The Safe Transport of Spent Nuclear Fuel and High-Level Radioactive Waste in the United States - Transportation Research Board; National Research Council
This new report from the National Research Council's Nuclear and Radiation Studies Board (NRSB) and the Transportation Research Board reviews the risks and technical and societal concerns for the transport of spent nuclear fuel and high-level radioactive waste in the United States. Shipments are expected to increase as the U.S. Department of Energy opens a repository for spent fuel and high-level waste at Yucca Mountain, and the commercial nuclear industry considers constructing a facility in Utah for temporary storage of spent fuel from some of its nuclear waste plants. The report concludes that there are no fundamental technical barriers to the safe transport of spent nuclear fuel and high-level radioactive and the radiological risks of transport are well understood and generally low. However, there are a number of challenges that must be addressed before large-quantity shipping programs can be implemented successfully. Among these are managing \

The Richard and Hinda Rosenthal Lectures 2003: Keeping Patients Safe – Transforming the Work Environment of Nurses (The National Academies Press, 2004)
Through the generosity of the Rosenthal Family Foundation (formerly the Richard and Hinda Rosenthal Foundation), a discussion series was created to bring greater attention to some of the significant health policy issues facing our nation today. Each year a major health topic is addressed through remarks and conversation between experts in the field. The Institute of Medicine (IOM) later publishes the proceedings from this event for the benefit of a wider audience. This volume summarizes an engaging discussion on the IOM 2002 report, Keeping Patients Safe: Transforming the Work Environment of Nurses.

Airfield Pavement Markings: Effective Techniques for Removal and Temporary Applications - Transportation Research Board; National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2022)
Airfield markings are critical visual cues and are vital for runways and taxiways. During airfield construction projects, it is often required to remove or obliterate the existing pavement markings and apply temporary markings. These methods can leave scarring that is visible on the airfield for years. Such traces of former markings can be mistaken for active airfield markings by pilots and ground personnel. The TRB Airport Cooperative Research Program's ACRP Research Report 247: Airfield Pavement Markings: Effective Techniques for Removal and Temporary Applications provides airport operators with methods and procedures for removing old airfield markings as well as applying temporary markings. Supplemental to the report is the Contractor's Final Report on the project.

Assessment of Mars Science and Mission Priorities - National Research Council (The National Academies Press, 2003)
Within the Office of Space Science of the National Aeronautics and Space Administration (NASA) special importance is attached to exploration of the planet Mars, because it is the most like Earth of the planets in the solar system and the place where the first detection of extraterrestrial life seems most likely to be made. The failures in 1999 of two NASA missions2014Mars Climate Orbiter and Mars Polar Lander2014caused the space agency's program of Mars exploration to be systematically rethought, both technologically and scientifically. A new Mars Exploration Program plan (summarized in Appendix A) was announced in October 2000. The Committee on Planetary and Lunar Exploration (COMPLEX), a standing committee of the Space Studies Board of the National Research Council, was asked to examine the scientific content of this new program. This goals of this report are the following: -Review the state of knowledge of the planet Mars, with special emphasis on findings of the most recent Mars missions and related research activities; -Review the most important Mars research opportunities in the immediate future; -Review scientific priorities for the exploration of Mars identified by COMPLEX (and other scientific advisory groups) and their motivation, and consider the degree to which recent discoveries suggest a reordering of priorities; and -Assess the congruence between NASA's evolving Mars Exploration Program plan and these recommended priorities, and suggest any adjustments that might be warranted.

Meeting the Challenge of Caring for Persons Living with Dementia and Their Care Partners and Caregivers: A Way Forward - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2021)
Millions of people are living with dementia in the United States and globally. To live well with dementia, people need care, services, and supports that reflect their values and preferences, build on their strengths and abilities, promote well-being, and address needs that evolve as cognitive impairment deepens. Persons living with dementia co-manage their care with or rely on the support of a wide range of care partners and caregivers, including spouses, other family members and friends, and direct care workers in homes or residential care settings. While dementia care has improved since the 1970s, many individuals still lack access to high-quality care and are not living as well as they might. Disadvantaged groups, especially racial and ethnic minorities, still face challenges in access to care, services, and supports, due to deep and persistent inequities. Meeting the Challenge of Caring for Persons Living with Dementia and Their Care Partners and Caregivers: A Way Forward examines the complex body of evidence on dementia care and informs decision making about which interventions are ready to be broadly disseminated and implemented. It also offers a blueprint to guide future research using rigorous, cutting-edge methods that are inclusive, equitable, and yield critical information for real-world implementation, toward the ultimate goal of better supporting persons living with dementia and their care partners and caregivers in living as well as possible.

Multimodal Fare Payment Integration - Transportation Research Board; National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2020)
Nearly all transit agencies are seeing potential benefits to multimodal payment convergence. However, many agencies find that implementing necessary upgrades is cost-prohibitive, which is the biggest barrier to full adoption.The TRB Transit Cooperative Research Program's TCRP Synthesis 144: Multimodal Fare Payment Integration documents current practices and experiences of transit agencies dealing with the complexities of multimodal fare payment convergence.

Fare Capping: Balancing Revenue and Equity Impacts - Transportation Research Board; National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2022)
Transit agencies in the United States are beginning to experiment with fare caps to ensure that passengers who pay for single rides do not pay more than multiple-ride passes included in their fare structure.The TRB Transit Cooperative Research Program's TCRP Synthesis 160: Fare Capping: Balancing Revenue and Equity Impacts includes a review of the literature; a survey of 35 North American transit agencies that have recently considered implementing, are in the planning stages of implementing, or have implemented fare capping; and detailed case examples for five transit agencies that provide greater insight into the motivations, program designs, implementations, and lessons learned.

The Challenges and Opportunities of Advance Care Planning: Proceedings of a Workshop - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2021)
Advance Care Planning(ACP)has long been a staple of caring for people with serious illness. Over its history, it has been defined in different ways. Clinicians, researchers, patients, and the public have developed a variety of perspectives about the many aspects of ACP, ranging from the definition to the timing, goals, outcomes, and value of ACP. To better understand the challenges and opportunities for ACP, acknowledge and highlight divergent viewpoints, and examine what is empirically known and not known about ACP and its outcomes, the National Academies of Sciences, Engineering, and Medicine's Roundtable on Quality Care for People with Serious Illness hosted a virtual public workshop, Advance Care Planning: Challenges and Opportunities, on October 26 and November 2, 2020. The workshop explored the paradox of ACP, its evidence base, ways to think differently about ACP, and various approaches to making it more effective.This Proceedings of a Workshop summarizes the presentations and discussions from that workshop.

Review of Four CARA Programs and Preparing for Future Evaluations - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2023)
The Comprehensive Addiction and Recovery Act (CARA; P.L. 114-198) was signed into law in 2016 to help address the challenges of overdose deaths and opioid use disorder, and to expand access to evidence-based treatment. Among these efforts was the authorization of four grant programs to be overseen by the Substance Abuse and Mental Health Services Administration (SAMHSA). In 2018, SAMHSA requested that the National Academies establish a committee to conduct a review of the four programs, which focus primarily on opioids, but occasionally include treatment and recovery services for co-occurring substance use disorders. The review resulted in three consensus study reports over five years. This third and final report aims to (1) understand the processes of the four grant programs; actions taken by grantees and their partners; impacts to clients, patients, the community, and public; and structural or environmental changes that might have resulted from grant funding, and (2) analyze how future congressionally mandated evaluations can be structured and carried out to better support policy makers.

Childhood Cancer and Functional Impacts Across the Care Continuum - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2021)
Since the late 1960s, the survival rate in children and adolescents diagnosed with cancer has steadily improved, with a corresponding decline in the cancer-specific death rate. Although the improvements in survival are encouraging, they have come at the cost of acute, chronic, and late adverse effects precipitated by the toxicities associated with the individual or combined use of different types of treatment (e.g., surgery, radiation, chemotherapy). In some cases, the impairments resulting from cancer and its treatment are severe enough to qualify a child for U.S. Social Security Administration disability benefits. At the request of Social Security Administration, Childhood Cancer and Functional Impacts Across the Care Continuum provides current information and findings and conclusions regarding the diagnosis, treatment, and prognosis of selected childhood cancers, including different types of malignant solid tumors, and the effect of those cancers on children2019s health and functional capacity, including the relative levels of functional limitation typically associated with the cancers and their treatment. This report also provides a summary of selected treatments currently being studied in clinical trials and identifies any limitations on the availability of these treatments, such as whether treatments are available only in certain geographic areas.

Genomic Epidemiology Data Infrastructure Needs for SARS-CoV-2: Modernizing Pandemic Response Strategies - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2020)
In December 2019, new cases of severe pneumonia were first detected in Wuhan, China, and the cause was determined to be a novel beta coronavirus related to the severe acute respiratory syndrome (SARS) coronavirus that emerged from a bat reservoir in 2002. Within six months, this new virus2014SARS coronavirus 2 (SARS-CoV-2)2014has spread worldwide, infecting at least 10 million people with an estimated 500,000 deaths. COVID-19, the disease caused by SARS-CoV-2, was declared a public health emergency of international concern on January 30, 2020 by the World Health Organization (WHO) and a pandemic on March 11, 2020. To date, there is no approved effective treatment or vaccine for COVID-19, and it continues to spread in many countries. Genomic Epidemiology Data Infrastructure Needs for SARS-CoV-2: Modernizing Pandemic Response Strategies lays out a framework to define and describe the data needs for a system to track and correlate viral genome sequences with clinical and epidemiological data. Such a system would help ensure the integration of data on viral evolution with detection, diagnostic, and countermeasure efforts. This report also explores data collection mechanisms to ensure a representative global sample set of all relevant extant sequences and considers challenges and opportunities for coordination across existing domestic, global, and regional data sources.

Assessment of NASA's Mars Architecture 2007-2016 - National Research Council (The National Academies Press, 2006)
The United States and the former Soviet Union have sent spacecraft to mars as early as 1966, with Mars' exploration being priority for NASA spacecraft. Both sides, however, have failed as well as succeed. The inability to determine if life exists on Mars is considered one of NASA's failures and undercut political support for additional Mars missions in the U.S. until the launch of the Mars Observer in 1992. Thus, the exploration of life on Mars continues, but with a new approach. Assessment of NASA's Mars Architecture, 2007-2016 is an assessment by the Committee to Review the Next Decade Mars Architecture of the National Research Council (NRC) conducted by request of Dr. Mary Cleave, NASA's Associate Administrator for the Science Mission Directorate. The Committee addresses the following questions: Is the Mars architecture reflective of the strategies, priorities, and guidelines put forward by the National Research Council's solar system exploration decadal survey and related science strategies and NASA plans?, Does the revised Mars architecture address the goals of NASA's Mars Exploration Program and optimize the science return, given the current fiscal posture of the program?, and Does the Mars architecture represent a reasonably balanced mission portfolio? After several months of study, consideration and incorporation of the guidance from NRC studies, especially New Frontiers in the Solar System, and the Vision for Space Exploration; community consultations via individual inputs; and a MEPAG-sponsored working group, a plan was created. This report includes the plan, which has an Astrobiology Field Laboratory or two Mild Rovers mission planned for 2016, recommendations from the committee, NRC guidelines for mars exploration, and more.

Effective Removal of Pavement Markings - Transportation Research Board; National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2013)
TRB2019s National Cooperative Highway Research Program (NCHRP) Report 759: Effective Removal of Pavement Markings aids in the selection of safe, cost-effective, and environmentally acceptable practices for the removal of work zone and permanent pavement markings. The practices highlighted in this report emphasize minimal damage to the underlying pavement or visible character of the surface course.

Reimagining a System of Care to Promote the Well-Being of Children and Families: Proceedings of a Workshop - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2021)
The economic and physical and health impacts of the COVID-19 pandemic were disproportionately borne by Black, Hispanic, and Native Americans. The true impacts on children and families may not be fully known until after the pandemic ends, but many agree that a new system of care is needed to promote the well-being of children and families in the pandemic2019s aftermath. On September 14-15, 2020, the National Academies of Sciences, Engineering, and Medicine2019s Forum for Children2019s Well-Being organized a workshop focused on building systems to support children and families in the aftermath of the COVID-19 pandemic. Workshop speakers and organizers paid particular attention to how economic, behavioral, and public health systems that can combat racism and promote the well-being of children and families. Participants engaged in discussionsabout a broad range of existing tools and resources that could be used to further promote family well-being and health equity in the United States.

Guidebook and Research Plan to Help Communities Improve Transportation to Health Care Services - Transportation Research Board; National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2021)
The availability of transportation influences the ability of individuals to access health care, whether in urban, suburban or rural areas. Those lacking appropriate or available transportation miss health care appointments, resulting in delays in receiving medical interventions that can lead to poorer health outcomes. This in turn contributes to the rising cost of health care.The TRB Transit Cooperative Research Program's TCRP Research Report 223: Guidebook and Research Plan to Help Communities Improve Transportation to Health Care Services details how to initiate a dialogue between transportation and health care providers as well as subsequent actions and strategies for pursuing a partnership and implementing transportation solutions appropriate for patients.Efforts to improve health in the United States increasingly recognize that it2019s not just the health care system that is responsible. It2019s a range of factors that collectively affect health and health outcomes. These factors are known as the 201csocial determinants of health,201d and, significantly, they include transportation.

Business Models for Mobile Fare Apps - Transportation Research Board; National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2020)
Five different business models for mobile fare payment apps are examined, as the world of apps used by transit agencies in the United States and Canada continues to steadily grow.The TRB Transit Cooperative Research Program's TCRP Synthesis 148: Business Models for Mobile Fare Apps documents current practices and experiences of transit agencies that offer mobile fare payment applications to transit riders.The report includes case examples from six cities: Santa Monica, Denver, Austin, Chicago, Dallas, and Ontario, Canada.

Innovation in Cancer Care and Cancer Research in the Context of the COVID-19 Pandemic: Proceedings of a Workshop - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2022)
The COVID-19 pandemic has led to dramatic adjustments in cancer care delivery and cancer research. To examine these changes, the National Cancer Policy Forum of the National Academies of Sciences, Engineering, and Medicine convened a virtual workshop, Innovation in Cancer Care and Cancer Research in the Context of the COVID-19 Pandemic, in July 2021. Workshop speakers considered the lessons learned from these adaptations in order to improve the delivery of high-quality cancer care and the conduct of cancer clinical trials in the post-pandemic era. This Proceedings of a Workshop highlights presentations and discussions from the workshop.

Essential Health Care Services Addressing Intimate Partner Violence - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2024)
A National Academies committee was tasked with identifying essential health care services for women related to intimate partner violence (IPV) during steady state conditions, determining whether the essential health care services related to IPV differ during public health emergencies (PHEs), and identifying strategies to sustain access to those essential health care services during PHEs. This report, Essential Health Care Services Addressing Intimate Partner Violence, presents findings from research and deliberations and lays out recommendations for leaders of health care systems, federal agencies, health care providers, emergency planners, and those involved in IPV research.